Skills Development for Inclusive and Sustainable Growth in Developing Asia-Pacific - Maclean, Rupert; Jagannathan, Shanti; Sarvi, Jouko (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2013)
Focusing on the Asia-Pacific region, which in recent years has been the engine of global economic growth , this volume surveys trends and prospects in technical and vocational education and training (TVET) with particular reference to achieving inclusive growth and the greening of economies. Underlying the increasing pressure for new models of TVET provision is the rapid pace of technological change, demand for a work force which is highly responsive to evolving needs and a transforming market place that calls for higher order skills and lifelong learning. The book proposes a re-engineered, modernized TVET system that fosters an innovative approach which enhances the employability of workers as well as the sustainability of their livelihoods. The book includes contributions from leading policy makers, researchers, and practitioners, including those in the private sector in analyzing and forecasting the most urgent priorities in skills development. The book argues for creative approaches to TVET design and delivery particularly with a view to improve job prospects , and meeting the goals of inclusion, sustainable development and social cohesion. Addressing issues such as the chronic mismatches between skills acquired and actual skills required in the work place, the volume proposes diversified approaches towards workforce development and partnerships with the private sector to improve the quality and relevance of skills development . The new imperatives created by 'greening' economies and responses required in skills development and training are addressed. Developing TVET is a high priority for governments in the Asia Pacific region as they seek to achieve long-term sustainable growth since the .continued success of their economic destinies depend on it. The volume also includes an emerging framework for skills development for inclusive and sustainable growth in the Asia and Pacific region.